Role of endoscopic evaluation prior to diagnostic transesophageal echocardiography: Is it necessary?. Issue 9 (19th July 2022) - Sandhu, Sunny; Alhankawi, Dhuha; Roytman, Marina; Jain, Ratnali; Prajapati, Devang
Abstract: Background and Aim: Esophagogastroduodenoscopy (EGD) is often performed prior to transesophageal echocardiogram (TEE) to evaluate for esophageal pathologies. Although TEE is a safe procedure, some contraindications exist, such as esophageal varices. The incidence of bleeding with TEE is <0.01%, which questions the need for this routine invasive procedure prior to TEE. We sought to characterize patients in whom pre‐TEE endoscopy was requested to determine its clinical utility and identify those that would most benefit. Methods: We retrospectively studied patients who underwent EGD for TEE clearance between January 2014 and October 2019. We assessed how often EGD changed management and complications after TEE in those with EGD abnormalities. Results: Eighty‐three patients were included. Twenty‐three percent had prior GI bleed, 63% had cirrhosis, 18% had known varices, and 7% had prior variceal bleed. The most common EGD findings were varices (33%). Eighty‐one percent proceeded with TEE. Reasons for TEE deferral included varices (12.5%), high‐risk bleeding lesion (12.5%), and mechanical abnormality (12.5%). In the majority (37.5%), TEE was deemed no longer indicated. No patient undergoing TEE had significant hemoglobin drop or overt bleeding. The most common reason for not performing TEE was unrelated to EGD findings: lack of ongoing indication for TEE. Conclusion: Based on our study, EGD is likely not needed for TEE clearance in patients with varices or prior GI bleed. Given that data are limited in patients with abnormalities such as strictures, EGD may still be warranted for these patients. Further studies to identify which patients will benefit from pre‐TEE endoscopy are warranted. Abstract : Esophagogastroduodenoscopy (EGD) is often performed prior to transesophageal echocardiogram (TEE) to evaluate for esophageal pathologies. Based on our study, EGD is likely not needed for TEE clearance in patients with varices or prior GI bleed.